Icariside II attenuates cardiac remodeling via AMPKα2/mTORC1 in vivo and in vitro - Xiao-Yu Liu; Hai-han Liao; Hong Feng; Nan Zhang; Jing-jing Yang; Wen-jing Li; Si Chen; Wei Deng; Qi-Zhu Tang (Elsevier, 2018)
Icariside II (ICA II), a flavonoid derived from Epimediumbrevicormum Maxin in, has multiple biological activities in Chinese traditional medicine. Our study aimed to investigate the potential activity of ICA II against cardiac remodeling and the underlying mechanism. Mice received aorta banding (AB) or sham surgery, and then were randomly divided into ICA II or vehicle (veh) group for 6 weeks. After echocardiography and pressure-volume loop examination, hearts were harvested for histopathological analysis and molecular mechanism investigation. Additionally, neonatal rat cardiomyocytes (NRCM) were used for in vitro experiments. ICA II attenuated the systolic and diastolic cardiac dysfunction, and protected mouse heart from hypertrophy and fibrosis. The underlying mechanism might involve in the regulation of Akt, AMPKα and mTORC. In in vitro experiment, ICA II prevented phenylephrine (PE) induced NRCM hypertrophy by regulating AMPKα/mTORC pathway. This protective effect was disappeared after treatment with Compound C (CpC), an AMPKα inhibitor. Moreover, ICA II activated AMPK at baseline. ICAII was superior to resveratrol in activating AMPKα and similar to AICAR. ICA II protected against cardiac remodeling and NRCM hypertrophy by regulating AMPK/mTORC pathway. ICA II may be a candidate for the treatment of malignant cardiac remodeling. Keywords: Icariside II, Cardiac remodeling, AMPK/mTORC, Cardiomyocyte